Merozoite surface protein 1 paralog is involved in the human erythrocyte invasion of a zoonotic malaria, Plasmodium knowlesi - Lee, Seong-Kyun; Nguyen, Tuyet Kha; Mohring, Franziska; Han, Jin-Hee; Firdaus, Egy Rahman; Na, Sung-Hun; Park, Won-Sun; Moon, Robert W.; Han, Eun-Taek (Frontiers in Cellular and Infection Microbiology, 2023)
The zoonotic malaria parasite Plasmodium knowlesi is an important public health concern in Southeast Asia. Invasion of host erythrocytes is essential for parasite growth, and thus, understanding the repertoire of parasite proteins that enable this process is vital for identifying vaccine candidates and how some species are able to cause zoonotic infection. Merozoite surface protein 1 (MSP1) is found in all malaria parasite species and is perhaps the most well-studied as a potential vaccine candidate. While MSP1 is encoded by a single gene in P. falciparum, all other human infective species (P. vivax, P. knowlesi, P. ovale, and P. malariae) additionally encode a divergent paralogue known as MSP1P, and little is known about its role or potential functional redundancy with MSP1. We, therefore, studied the function of P. knowlesi merozoite surface protein 1 paralog (PkMSP1P), using both recombinant protein and CRISPR-Cas9 genome editing. The recombinant 19-kDa C-terminus of PkMSP1P (PkMSP1P-19) was shown to bind specifically to human reticulocytes. However, immunoblotting data suggested that PkMSP1P-19-induced antibodies can recognize PkMSP1-19 and vice versa, confounding our ability to separate the properties of these two proteins. Targeted disruption of the pkmsp1p gene profoundly impacts parasite growth, demonstrating for the first time that PkMSP1P is important in in vitro growth of P. knowlesi and likely plays a distinct role from PkMSP1. Importantly, the MSP1P KO also enabled functional characterization of the PkMSP1P-19 antibodies, revealing clear immune cross-reactivity between the two paralogues, highlighting the vital importance of genetic studies in contextualizing recombinant protein studies.